Analysis of Dowel Action in Reinforced Concrete Beams with Shear Reinforcement - Joshi Sreenivasa Prasad; Poluraju P.; Singh Umesh K. (Civil and Environmental Engineering, 2021)
The shear transfer mechanism was examined to view the contributions of different components of shear transfer such as aggregate interlocking, dowel force and uncracked compression zone. Understanding the role of various shear transfer components with transverse reinforcement provided was complex due to traditional difficulties involved in detail assessment of accompanying kinematics during the failure. In the present paper, the issue was addressed by employing sixteen specimens and grouped under two categories representing conventional beams and beams with preformed cracks and were tested under four - point bending load with a shear span to depth ratio of 1.26 by increasing the characteristic strength of concrete. From the results obtained, empirical formulas proposed were also evaluated and it was concluded that the results were consistent and contribution of shear transfer across uncracked compression zone was maximum in shear resistance with transverse reinforcement provided. Later structural behaviour was also assessed and it was concluded that beams with preformed cracks had exhibited greater stiffness thus nullifying the effect of aggregate interlocking in shear transfer.